Autophagy as a gateway for the effects of methamphetamine: From neurotransmitter release and synaptic plasticity to psychiatric and neurodegenerative disorders. (September 2021) - Limanaqi, Fiona; Busceti, Carla L.; Celli, Roberta; Biagioni, Francesca; Fornai, Francesco
Highlights: Autophagy modulates neurotransmitter release, synaptic plasticity, and neuronal survival. METH impairs the autophagy machinery by altering LC3 compartmentalization. Autophagy impairment fosters abnormal DA transmission and proteinopathy. METH-induced autophagy impairment fosters maladaptive plasticity and neurotoxicity. Autophagy bridges drug abuse, psychiatric manifestations, and neurodegenerative phenomena. Abstract: As a major eukaryotic cell clearing machinery, autophagy grants cell proteostasis, which is key for neurotransmitter release, synaptic plasticity, and neuronal survival. In line with this, besides neuropathological events, autophagy dysfunctions are bound to synaptic alterations that occur in mental disorders, and early on, in neurodegenerative diseases. This is also the case of methamphetamine (METH) abuse, which leads to psychiatric disturbances and neurotoxicity. While consistently altering the autophagy machinery, METH produces behavioral and neurotoxic effects through molecular and biochemical events that can be recapitulated by autophagy blockade. These consist of altered physiological dopamine (DA) release, abnormal stimulation of DA and glutamate receptors, as well as oxidative, excitotoxic, and neuroinflammatory events. Recent molecular insights suggest that METH early impairs the autophagy machinery, though its functional significance remains to be investigated. Here we discuss evidence suggesting that alterations of DA transmission and autophagy are intermingled within a chain of events underlying behavioral alterations and neurodegenerative phenomena produced by METH. Understanding how METH alters the autophagy machinery is expected to provide novel insights into the neurobiology of METH addiction sharing some features with psychiatric disorders and parkinsonism.